How valuable is exchange rate flexibility? Optimal monetary policy under sectoral shocks - Cédric Tille (Federal Reserve Bank of New York, 2002)
The paper explores the optimal monetary policy reaction to productivity shocks in an open economy. Whereas earlier studies assume that countries specialize in producing particular goods, I enrich the analysis by allowing for incomplete specialization. I confirm the finding of Obstfeld and Rogoff (2000)—who build on Friedman (1953)—that a flexible exchange rate is highly valuable in delivering the optimal response to country- specific shocks. Its value is, however, much smaller when shocks are sector-specific, because exchange rate fluctuations then lead to misallocations between different firms within a sector. The limitation on the value of flexibility is sizable even when specialization is high.
Keywords: F31; F41; F42; 330; optimal monetary policy; exchange rate flexibility; competitiveness; Geldpolitik; Schock; Produktivität; Internationale Arbeitsteilung; Außenhandelsstruktur; Flexibler Wechselkurs; Wohlfahrtsanalyse; Theorie